2009
DOI: 10.1073/pnas.0906267106
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidification exerts opposite actions on TREK1 and TREK2 potassium channels via a single conserved histidine residue

Abstract: Mechanosensitive K ؉ channels TREK1 and TREK2 form a subclass of two P-domain K ؉ channels. They are potently activated by polyunsaturated fatty acids and are involved in neuroprotection, anesthesia, and pain perception. Here, we show that acidification of the extracellular medium strongly inhibits TREK1 with an apparent pK near to 7.4 corresponding to the physiological pH. The all-ornone effect of pH variation is steep and is observed within one pH unit. TREK2 is not inhibited but activated by acidification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
149
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 42 publications
5
149
0
Order By: Relevance
“…5 B and C). In contrast to TREK2, TRAAK is inhibited by external acidification, but more weakly than TREK1 (11). As expected, TREK1-TRAAK was inhibited by external acidification but the observed inhibition was intermediate in amplitude between what is seen in TREK1 (highly sensitive) and TRAAK (poorly sensitive) (Fig.…”
Section: Trek1 and Trek2 Coassemble And Are Targeted To The Plasmasupporting
confidence: 70%
See 1 more Smart Citation
“…5 B and C). In contrast to TREK2, TRAAK is inhibited by external acidification, but more weakly than TREK1 (11). As expected, TREK1-TRAAK was inhibited by external acidification but the observed inhibition was intermediate in amplitude between what is seen in TREK1 (highly sensitive) and TRAAK (poorly sensitive) (Fig.…”
Section: Trek1 and Trek2 Coassemble And Are Targeted To The Plasmasupporting
confidence: 70%
“…Intracellular acidification stimulates both TREK1 and TREK2 (8,9), whereas TRAAK is stimulated by intracellular alkalinization (10). In contrast, extracellular acidification is able to inhibit TREK1 and TRAAK, but activates TREK2 (11). Members of the TREK channel subfamily are also regulated extensively by intracellular scaffolding and signaling proteins (10).…”
mentioning
confidence: 99%
“…Although the IRK1 channel differs from TREK1 in its selectivity for PI (4,5)P2, it appears to have a common mechanism of channel regulation in that channel activity is enhanced when the IRK1 C terminus associates with the membrane and is reduced when PI(4,5)P2 levels drop and the C terminus dissociates from the membrane. Thus, it appears that dissociation from the membrane of the C terminus of a channel may be a general mechanism of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This current drives the membrane potential toward the K + equilibrium potential and thus affects input resistance. TREK1 displays low basal activity when expressed alone (1) but can be strongly stimulated by temperature (2), mechanical stretch (3), external alkalization (4), intracellular acidification (5), polyunsaturated fatty acids (PUFAs) (6), lysophospholipids (7), phosphatidylinositol-4,5-bisphosphate [PI (4,5)P2] (8,9), and pharmacological agents such as volatile anesthetics (10) and riluzole (11). TREK1 is inhibited by neurotransmitters and hormones that activate Gq and Gs pathways (3,(12)(13)(14) and pharmacological agents such as the antidepressant drug fluoxetine (15).…”
mentioning
confidence: 99%
“…Changes of extracellular pH may modulate the activities of ion channels. It has been reported that extracellular acidification inhibited inwardly rectifying potassium channels (11,15,30), mechanosensitive potassium channel (or tandem pore domain potassium channel) TREK1 (25), intracellular calcium-activated potassium channel K Ca 2.2 and K Ca 2.3 (24), the voltage-gated potassium channel Kv1.5 (14), human ether-à-go-go potassium channel (6) and voltage-dependent Ca 2ϩ channel (1), but activated mechanosensitive potassium channel TREK2 (25) and modulated the activities of ATP-sensitive potassium channel (12). The effects of pH changes on ion channels may be related to the protonation of histidine residues in the outer pore regions of channels, which have been reported to be proton interaction sites that regulate channel availability and inactivation (14,24,25).…”
mentioning
confidence: 99%